2006
DOI: 10.1534/genetics.106.060236
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role for Checkpoint Rad53 Protein Kinase in the Initiation of Chromosomal DNA Replication inSaccharomyces cerevisiae

Abstract: A novel role for Rad53 in the initiation of DNA replication that is independent of checkpoint or deoxynucleotide regulation is proposed. Rad53 kinase is part of a signal transduction pathway involved in the DNA damage and replication checkpoints, while Cdc7-Dbf4 kinase (DDK) is important for the initiation of DNA replication. In addition to the known cdc7-rad53 synthetic lethality, rad53 mutations suppress mcm5-bob1, a mutation in the replicative MCM helicase that bypasses DDK's essential role. Rad53 kinase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 81 publications
(130 reference statements)
3
54
0
Order By: Relevance
“…Although the Dbf4-ND109 protein both binds to and activates Cdc7 normally , it is defective for binding Cdc5 and Rad53 (this study). Therefore, we tested whether the synthetic lethality between dbf4-NΔ109 and rad53-1 was due to the loss of the Dbf4-Cdc5 or Dbf4-Rad53 interactions.We first sequenced the rad53-1 gene (Weinert et al 1994) and found a single G653E point mutation, which is identical to that reported for the rad53-11 allele (Dohrmann and Sclafani 2006). G653 falls within a loop between the b6 and b7 strands of the FHA2 domain ( Figure 5A) and is adjacent to the conserved N655 residue, which plays an important role in substrate recognition (Byeon et al 2001).…”
supporting
confidence: 66%
See 3 more Smart Citations
“…Although the Dbf4-ND109 protein both binds to and activates Cdc7 normally , it is defective for binding Cdc5 and Rad53 (this study). Therefore, we tested whether the synthetic lethality between dbf4-NΔ109 and rad53-1 was due to the loss of the Dbf4-Cdc5 or Dbf4-Rad53 interactions.We first sequenced the rad53-1 gene (Weinert et al 1994) and found a single G653E point mutation, which is identical to that reported for the rad53-11 allele (Dohrmann and Sclafani 2006). G653 falls within a loop between the b6 and b7 strands of the FHA2 domain ( Figure 5A) and is adjacent to the conserved N655 residue, which plays an important role in substrate recognition (Byeon et al 2001).…”
supporting
confidence: 66%
“…We first sequenced the rad53-1 gene (Weinert et al 1994) and found a single G653E point mutation, which is identical to that reported for the rad53-11 allele (Dohrmann and Sclafani 2006). G653 falls within a loop between the b6 and b7 strands of the FHA2 domain ( Figure 5A) and is adjacent to the conserved N655 residue, which plays an important role in substrate recognition (Byeon et al 2001).…”
supporting
confidence: 66%
See 2 more Smart Citations
“…As an initial approach to understanding how srp1 mutants might affect DNA replication, we utilized a plasmid loss assay (Friedman et al 1996;Dohrmann and Sclafani 2006). This assay monitors loss of plasmids containing an ARS, which function as replication origins in S. cerevisiae (Dohrmann and Sclafani 2006).…”
Section: Resultsmentioning
confidence: 99%